2020
DOI: 10.1016/j.ijid.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of influenza, RSV, and other respiratory infections among children in Qatar: A six years report (2012–2017)

Abstract: Background: Studies on the etiology of respiratory infections among children in Qatar and surrounding countries are limited. Objectives: To describe the prevalence and seasonality of RSV, influenza, and other respiratory pathogens among children in Qatar. Methods: We retrospectively collected and analyzed data of 33,404 children (<15 years) presented with influenza-like illness from 2012 to 2017. Results: At least one respiratory pathogen was detected in 26,138 (78%) of patients. Together, human rhinoviruses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
7
16
0
1
Order By: Relevance
“…Two studies used surveillance samples [ 21 , 26 ]. Sixteen studies reported HCoV infection by screening all 4 subtypes of virus [ 5 , 7 , 9–11 , 13 , 14 , 16–22 , 24 , 25 ]. The range of proportions of positive specimens was 0.2%–18.4% (median: 4.45%) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies used surveillance samples [ 21 , 26 ]. Sixteen studies reported HCoV infection by screening all 4 subtypes of virus [ 5 , 7 , 9–11 , 13 , 14 , 16–22 , 24 , 25 ]. The range of proportions of positive specimens was 0.2%–18.4% (median: 4.45%) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A small number of studies reported peaks during summer months (June, 4.1%; July, 4.1%; and August, 2.0%) [ 5 , 6 , 13 , 14 , 17 ]. Around 38.8% of observation periods showed that more than 5% of specimens tested positive for HCoVs in February and March [ 5 , 7 , 8 , 10–12 , 16 , 17 , 19–26 ]. Around 10 to 22% of observation periods showed that more than 5% of specimens had positive test results during fall (September, 10.2%; October, 12.2%; and November, 22.4%) [ 5–8 , 10 , 12 , 17 , 19 , 20 , 23 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies, RSV detection was more than 3 times greater than the next leading pathogen [ 14 ]. Reported RSV positivity rates in tropical Asian countries range from 9% to 50% depending on the geographic location and sample population ( Table 1 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Not unexpectedly, an increased risk for RSV infection has been noted in infants with chronic lung disease, neurodevelopmental conditions and congenital heart disease, with repeated infections associated with asthma and atopy among the children and their families [ 15 ].…”
Section: Rsv Disease Activity Across Tropical Asiamentioning
confidence: 99%